Study of prevalence and types of anemia in primary hypothyroidism - Yadav, Rakesh K.; Ahmad, Mansoor; Mathur, Manoj K.; Dhingra, Vishal (International Journal of Advances in Medicine, 2019)
Background: Hypothyroidism is common disease with varying frequency between countries. Anemia in hypothyroidism can be normocytic normochromic, microcytic hypochromic and macrocytic hypochromic. Anemia severity is associated with hypothyroidism degree. Objective of this study to study the association between anemia and hypothyroidism and prevalence and types of anemia in primary hypothyroidism (subclinical and overt both). Methods: This cross sectional study was carried out at tertiary care hospital in North India. Newly diagnosed 100 primary hypothyroid patients and 100 controls with age and sex matched evaluated for anemia. Prevalence and types of anemia were studied and severity of anemia was correlated with that of hypothyroidism. Results: Anemia was observed in 90 patients with hypothyroidism. Symptoms due to anemia were higher in cases than in controls. RBCs morphology showed normocytic normochromic in 59, microcytic hypochromic in 26 and macrocytic hypochromic in 15 cases. Serum anti-TPO positivity was present in 71.1% in cases as compared to 33.33% in controls. Anemia was severe in cases with high TSH. Conclusions: Anemia was more prevalent in cases of hypothyroidism than in euthyroid controls. Normocytic normochromic type of anemia was most common type in this study. Serum anti-TPO positivity was 71.1% in cases. There was statistically significant negative correlation between TSH and haemoglobin. Symptoms of anemia were more in hypothyroid patients than in euthyroid anemic patients.